Comparison of Saliva and Nasopharyngeal Swab Nucleic Acid Amplification Testing for Detection of SARS-CoV-2 - Guillaume Butler‐Laporte; Alexander Lawandi; Ian Schiller; Mandy Yao; Nandini Dendukuri; Emily G. McDonald; Todd C. Lee (2021)
Nasopharyngeal swab nucleic acid amplification testing (NAAT) is the noninvasive criterion standard for diagnosis of coronavirus disease 2019 (COVID-19). However, it requires trained personnel, limiting its availability. Saliva NAAT represents an attractive alternative, but its diagnostic performance is unclear.